Le service public audiovisuel et sa régulation dans le REFRAM : une étude exploratoire des relations entre médias de service public et régulateurs - El Hadji Malick Ndiaye (Communiquer)
This research studies the audiovisual public service media's missions and the control national regulators exert within the national frameworks of 18 Europeans, Africans and Middle Eastern members of the French-speaking association of media regulators, using data collected in 2019 from each country's regulatory bodies. On the one hand, it provides an overview of the missions assigned to the public service media and their difficulties in ensuring them. On the other hand, it addresses the regulation that is applied to these public service media through the prism of control methods and the relationships that regulators and the media maintain.